Sustainable energy planning of residential sector: A case study of Bhanu municipality - Adhikari, Dibya; Shakya, Shree Raj; Bhattarai, Nawraj; Gaire, Yagya Prasad (Journal of Innovations in Engineering Education, 2021)
This study analyzes the energy situation of Bhanu Municipality, Tanahun, Nepal and deals for future energy projection and sustainable energy planning. Municipality occupies an area of 184 sq. km. This research is mainly based on primary data and supported by secondary data from various sources. For collection of primary data, 152 random household samples were surveyed and the locals were interviewed on their annual consumption. Data analysis was done with the help of excel and LEAP software. Major energy sources in the Municipality are forests, water resource, agricultural residues, animal dung and solar. Analysis shows that the total energy consumption of Bhanu municipality is 635.67TJ with per capita consumption is 12.69 GJ. The main fuel for cooking in the residential sector is firewood with share of  80% due to easily accessible from private, government and community forests which covers 38% of the municipality area. Lighting is done through grid electricity, almost 98% of the households has access to Grid. The analysis was made through different scenarios in LEAP i.e., Low Carbon Emission Scenario, Efficient Cooking Scenario, Efficient Lighting Scenario based on Municipal plans and Sustainable Goal 7.Low emission scenario is the policy intervention scenario in which electrification of end use demands is done for limiting the GHGs emissions.